The autonomous robotic environmental sensor (ARES). (26th November 2021) - Dyer, Benjamin; Biglarbegian, Mohammad; Aliabadi, Amir A.
Abstract : Measurement of thermal comfort in the indoor environment enables making adjustments to building design and operations to improve building performance. Methods of measurement tend to be tedious and expensive, requiring several expensive sensors to be mounted in the building. In this paper, we propose the Autonomous Robotic Environmental Sensor (ARES), a custom-designed omniwheel mobile robot retrofitted with several sensors capable of autonomously taking measurements of the indoor environment at multiple positions, reducing the number of sensors, amount of labor required, and cost. A Sliding Mode Controller (SMC) is designed and applied to the robotic platform, and positional accuracy is verified, allowing for highly accurate movement to ensure environmental measurements occur at known positions. Wind velocity, air temperature, and relative humidity data collected by the ARES platform in a laboratory environment for 24 hours is analyzed, providing insight into the thermo-fluid variables in the room and the room's predicted thermal comfort.